PERLAWANAN SASTRA DALAM CERPEN KORAN INDONESIA - Azwar Azwar (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
This paper discusses the resistance made by a writer against the oppression of the oppressed peoples. Poets in this case is an enlightened person who represents the voice of the community. The study was conducted on a short story titled